Transition conduction types of electrons in cryogenic media - Nazin, S.; Shikin, V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
Discussed in the paper are possibilities for description of electron conduction in transitional density range separating electron free and localized states in cryogenic media.